Análisis de los derechos laborales de los trabajadores para el cálculo de beneficios sociales en la contratación colectiva en Corporación Nacional de Electricidad CNEL. EP Bolívar, cantón Guaranda, año 2019 - Caluña Moposita, Lidia Alexandra (2019)
This research work was carried out with the purpose of developing a guide for calculating social benefits assigned by Law, as well as those obtained through collective contracting at the National Electricity Corporation CNEL. EP Bolívar. The methodology used corresponds to the descriptive research, which allowed to know the processes that are carried out in the calculation of the values to be paid by each worker, through the field research the information was collected through the surveys to the workers who work under collective agreement, interviews with the professional payroll and union secretary, to process and analyze the information obtained qualitative quantitative research is used. The results obtained show that workers do not have a clear knowledge of the concept of collective bargaining and the rights to which they are creditors for being part of this scheme, another situation is that the institution does not socialize the way of calculating the benefits that They perceive what creates discontent among workers. Therefore, we proceeded to design a guide for the calculation of social benefits in collective bargaining, which includes a detailed description of the items granted by the institution, legal basis, supporting documents and the procedure for determining the corresponding values. Once the research work is completed, a copy will be issued to the institution who, through prior analysis, will inform the workers, if possible, coordinate with the staff responsible for carrying out the socialization of the research results. Keywords: labor rights, social benefits, collective agreement, guide, procedure.